Pengaruh Metode Cooperative dan Self Confidence Terhadap Minat Berwirausaha Pada Siswa SMA Kota Bekasi - Lies Sunarmintyas; Dellia Mila Vernia (Peneliti.net, 2019)
An entrepreneur or entrepreneur is a person who is responsible for a business by bearing the risk of profit or loss. Entrepreneurs can be classified into two groups, namely business entrepreneurs (business entrepreneurs) and social entrepreneurs (social entrepreneurs). The main difference between them lies in the use of profits. For business entrepreneurs the benefits will be utilized for business expansion, while for social entrepreneurs the profits gained (in part or in whole) are reinvested in community empowerment. But the number of entrepreneurs is still below 2 percent of Indonesia's total population of 260 million. This research is using experimental method. Data is taken from vocational students. The purpose of this study is to find out the effect of Cooperative Learning Method and self confidence on the interest in entrepreneurship in Bekasi's Future Gate High School students. The results showed that, there was no significant effect of cooperative method and self confidence together on the interest in entrepreneurship and there was an effect of self confidence in the interest in entrepreneurship, and there was a significant effect of cooperative methods on entrepreneurial interest.